Evaluation of the effectiveness of low-intensity laser radiation for the occupational polyneuropathies’s​ treatment of the upper extremities - Greben'kov S.V.; Kochetova O.A. (Российская Арктика)
Abstract A feature of occupational polyneuropathies (OPP) of the upper extremities is the persistence of clinical and instrumental manifestations after cessation of contact with physical overload. The disease is relevant for the Arctic region, since the combined effect of the cooling microclimate leads to its occurrence in addition to the severity of the labor process. Low-intensity laser radiation (LILR) has a wide range of therapeutic effects, which allows it to be used in the treatment of various diseases of the nervous system. The purpose of the study is to evaluate the effectiveness of LILR in the treatment of professional PNP of the upper extremities with the determination of the main clinical and functional criteria of effectiveness.